Enhancing sustainable palm oil production: a roundtable on sustainable palm oil (RSPO) jurisdictional approach in Sabah and Central Kalimantan - Mark, Eugene Min Hui (Nanyang Technological University, 2024)
The Roundtable on Sustainable Palm Oil (RSPO) is an institution that promotes environmental sustainability norms in the palm oil sector and certifies individual plantations or mills. The thesis has sought to address the questions: 1) Why do Sabah and the Seruyan district in Central Kalimantan pursue an RSPO Jurisdictional Approach despite reservations at the national level? and 2) how much do subnational public and private elites see an RSPO Jurisdictional Approach as an opportunity to meet their objectives? Moreover, why do other subnational jurisdictions not pursue the approach? The thesis argues that an RSPO Jurisdictional Approach is implemented at the subnational level because there is a convergence of interests between subnational elites and RSPO in localising environmental sustainability norms. The research sheds light on the actors, processes, and outcomes at the subnational level, contributing to the literature on global norms. Using the New Interdependence Approach (NIA) as an analytical framework, the thesis utilised interviews, case study methods, and content analysis substantiated by secondary sources to support the findings. Apart from Sabah and Central Kalimantan, the study also explored cases in Sarawak and South Sumatra where actors chose not to pursue an RSPO Jurisdictional Approach. These case study comparisons allowed the research to uncover nuanced differences in the dynamics. The findings suggest that elites in Sabah and Central Kalimantan sees an RSPO Jurisdictional Approach as an opportunity to resolve local challenges such as smallholders’ technical capacity, community land conflicts, and broader conservation issues. However, their motivations are not solely driven by global expectations of improving environmental protection. Local political agendas also play a significant role in incentivising subnational elites towards an RSPO Jurisdictional Approach. Nevertheless, differences in the level of decentralised regulatory authority and civil society engagement can lead to asymmetries in power and resources. The thesis has emphasised the significance of personality-driven processes, thereby contributing how personal influence and leadership styles can influence norm localisation. Additionally, it encourages us to reconsider the roles of transnational actors, emphasising that RSPO plays only a supporting role in the Jurisdictional Approaches introduced in Sabah and Central Kalimantan.